PERAN VISI DALAM MENGAWAL PROSES REFORMASI JATI DIRI BANGSA - Chandra T. Putra (Jurnal Sosioteknologi, 2008)
Speaking of a nation's identity, should be influenced by what it did in the past, its present condition, and what vision it has for the future. Nation's identity needs to be continuously reformed. Since way back from independence, Indonesia has been through an up and down with its development progress. Its history and present condition should be managed into a vision that can mobilize its people to step onto a better future. This article is meant for capturing a flash look at Indonesian past and present, some visions that have arose in Indonesia, and how those visions would be meant for its citizens to interpret it.